“Ushered into the Kitchen”:: Lalia Halfkenny, Instructor of English and Elocution at a 19th-Century African American Women’s College - Harris, Jennifer (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2012)
This article examines the life of Lalia Halfkenny (1870-1897), the first identified black Maritimer to graduate from a post-secondary institution in the region (the Acadia Ladies’ College in 1889). Particular emphasis is on Halfkenny’s trajectory from illegitimacy and poverty in the region to respectability and security as an instructor of elocution at an all-black women’s institution in Richmond, Virginia. In so doing the article also discusses the experiences of other early black Maritime graduates and educators, with particular emphasis on the difficulties they encountered in obtaining rewarding employment in their home community and province as well as the consequences for other black Maritimers (who were denied the benefit of their contributions).